Enhancing the health and well-being of international students: insights from changes in their lifestyle post-COVID-19 - Ma, Jingru; Saita, Kazuya; Kaneko, Fumiko; Okamura, Hitoshi (Frontiers in Public Health, 2024)
IntroductionThe COVID-19 pandemic’s global impact has been profound, particularly for vulnerable populations, such as asylum seekers, refugees, and immigrants. Likewise, international students, who fall under the immigrant category umbrella, have faced considerable challenges throughout the pandemic. This study aimed to identify insights for enhancing Japanese international students’ health and well-being by investigating how epidemic prevention policies implemented by schools and the government influenced changes in their lifestyles during the post-pandemic era.MethodsSemi-structured interviews were conducted and inductive thematic analysis performed using NVivo software, to investigate the lifestyle changes of 20 (8 male and 12 female) international students (mean age: 31.5 years) at Hiroshima University, Japan, during the post-pandemic era.ResultsThe analysis revealed alterations in lifestyle habits and interpersonal relationships in the aftermath of the pandemic, with most international students continuing to practice some of the epidemic prevention and health behaviors they had adopted during the pandemic, including handwashing (n = 10), mask-wearing (n = 12), and physical distancing (n = 4), as a matter of habit. However, some of these epidemic prevention and health behaviors have not persisted as habits after the pandemic. However, there has been an increased emphasis on maintaining family relationships (n = 5).DiscussionAddressing language and information dissemination barriers that international students may encounter when accessing medical services, and providing them with employment guidance and support more suited to their current situation, are conducive to enhancing their health and well-being. Additionally, enhancing international students’ public awareness is crucial for safeguarding their health and preparing them for potential future public health emergencies.